PENGUNGKAPAN PERUBAHAN IKLIM: FAKTOR PENENTU DAN KONSEKUENSINYA TERHADAP NILAI PERUSAHAAN - Heri Pratama; Rita Wijayanti (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to examine the effect of financial performance, operational performance on climate change disclosure and firm value. The population in this study consisted of companies that are members of LQ45 on the Indonesia Stock Exchange (IDX). Samples were taken using purposive sampling method. This study uses multiple regression analysis for hypothesis testing. The results of this study indicate that financial performance and operational performance have a significant positive effect on climate change disclosure. And only financial performance and climate change disclosure have a significant positive effect on firm value.